Explaining drug-resistant infection in community pharmacies through effective information design. Issue 1 (2nd January 2020) - Walker, Sue; Hignett, Sue; Lim, Rosemary; Parkhurst, Caroline; Samuel, Flora
Abstract: This paper describes a research project in which information design, human factors, architecture and pharmacy academics worked with pharmacy professionals and pharmacy users to consider how to present information about antimicrobial resistance (AMR) in a community pharmacy setting. Project outcomes – as a result of an innovative design competition – included five different design solutions that explain aspects of AMR within the context of a community pharmacy. The project raised awareness in pharmacy professionals of how design can be used to challenge ideas and encourage new ways of thinking to communicate public health messages. Two winning prototype solutions were installed in a Day Lewis pharmacy in Reading and evaluated by pharmacists and pharmacy users. We make preliminary recommendations for effective health communication in community pharmacies.